Mercury and methylmercury in carapace of the marine turtle Caretta caretta, in northeastern Brazil and its potential for environmental monitoring - Rodriguez, César Augusto B. (2019)
The present work tests the use of carapace fragments of the marine turtle Caretta caretta as a tool for environmental biomonitoring of mercury (Hg) and to evaluate the influence of biological and ecological factors in Hg concentrations. Samples of carapace fragments were obtained during the nesting season of 2012 and 2016 and were analyzed for their total-Hg and methyl-Hg concentrations and the isotopic composition of carbon and nitrogen (δ15N and δ13C). Seventy-six females were sampled, with an average size of 87.1 to 107 cm of curved carapace length (CCL). The results showed a wide variation in total Hg concentrations (3.3 – 1,672 ng g-1) and low concentrations of methyl-Hg, not showing any pattern of accumulation among the individuals. The isotopic composition of δ15N and δ13C suggests that the individuals sampled belong to a high trophic level but did not present any relationship with the Hg concentrations. It suggests that, at least with the existing results, and unlike other turtle species, carapace fragments of C. caretta cannot yet be used in environmental monitoring.